ANALYSIS OF ONE-DIMENSIONAL SHEAR WAVE VELOCITY (Vs) MODEL FROM LOVE WAVE USING AMBIENT SEISMIC NOISE DATA AROUND PIDIE JAYA - INSAN APRILIAN (NIM:12313025), MUHAMMAD
Seismic interferometry is a relatively new method in seismology. This method utilizes the earth's ambient noise source to reconstruct the surface waves from cross-correlation of seismic recording between two stations. The cross-correlation result is an estimate of Green function that provides important information about subsurface conditions. The dispersive characters of surface wave can be analyzed in the time and frequency domain simultaneously to extract the Love wave group velocity as a function of frequency. Furthermore, depth-inversion of Love wave group velocity is applied to produce one-dimensional model of shear-wave velocity. The data are 9 aftershock records from temporary seismic network and 3 permanent BMKG stations of 1 month observations (December 2016-January 2017) around Pidie Jaya, Aceh. We produced 1-D model of shear wave velocity structure (Vs) from Love wave group velocity data for three cases of research coverage area using linearized least square inversion method. The resulted model has a positive correlation with the geological condition and the Crust 1.0 reference model. Based on the obtained solution, observed the low Vs value to a depth of 6 km, this can be associated with the presence of thick sediments layer in the area of Pidie Jaya, this explain the huge damage in that area caused by earthquake in 2016.